2009
DOI: 10.1094/phyto-99-8-0957
|View full text |Cite
|
Sign up to set email alerts
|

Association of Soil Chemical and Physical Properties with Pythium Species Diversity, Community Composition, and Disease Incidence

Abstract: A high-throughput baiting and identification process identified more than 7,000 isolates of Pythium from 88 locations in Ohio. Isolates were identified using direct-colony polymerase chain reaction followed by single-strand conformational polymorphism, and communities were assembled using the Jaccard similarity coefficient and cluster analysis. Both univariate and multivariate statistics were used to evaluate differences in soil properties between communities, and canonical discriminant analysis (CDA) was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(34 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…population densities between the soils but there may be differences in species composition that could have led to these soil response differences. Broders et al (6) reported that Pythium spp. richness and abundance varied among the 88 locations sampled.…”
Section: Discussionmentioning
confidence: 99%
“…population densities between the soils but there may be differences in species composition that could have led to these soil response differences. Broders et al (6) reported that Pythium spp. richness and abundance varied among the 88 locations sampled.…”
Section: Discussionmentioning
confidence: 99%
“…Pythium spp. are common plant pathogens that cause the disease root rot (Schroeder et al 2006, Broders et al 2009). The abundance of Pythium spp.…”
Section: Habitat-specific Community Structurementioning
confidence: 99%
“…The role of the latter on crop-disease interaction has been a serious matter of concern by many authors [25][28]. Regarding the soil, its physical and chemical properties play an important role in the plant health and the consequent disease occurrence and spread [29], [30]. In addition, crop management practices influence significantly the occurrence and control of hazelnut bacterial blight [31].…”
Section: Introductionmentioning
confidence: 99%
“…Their application has undergone a rapid expansion in plant disease epidemiology and management [48][52]. More specifically, spatial pattern analysis has been used to investigate factors affecting plant diseases [53][56]. The spread of plant diseases can be estimated by spatial interpolation methods, due to its relation with geographical variables such as soil and climatic characteristics [56].…”
Section: Introductionmentioning
confidence: 99%